Huangyusang decoction for Type 2 diabetes: A protocol for systematic review and meta analysis. Issue 8 (26th February 2021) - He, Peiyu; Zhang, Junyin; Gao, Tianyu; Wang, Yingxiang; Peng, Teng
Abstract: Background: Diabetes is a chronic metabolic disease characterized by elevated blood glucose levels due to insulin resistance and β-cell dysfunction. In China, Huangyusang decoction (HYS) has been widely used to treat Type 2 diabetes. However, there is no systematic review found. In order to evaluate the efficacy and safety of HYS in the treatment of Type 2 diabetes, we need to conduct a meta-analysis and systematic evaluation. Methods: We will enroll the randomized controlled trials (RCTs) evaluating the effectiveness and safety of HYS in the treatment of Type 2 diabetes. Data come mainly from 4 Chinese databases (CNKI, Wanfang, CBM, and VIP Database) and 4 English databases (PubMed, Embase, Cochrane Library, and Web of science). The enrollment of RCTs is from the starting date of database establishment till January 30, 2021. Fasting blood glucose is considered as the main indicator of the dyslipidemia, while the body mass index, glycated hemoglobin, fasting insulin, triglycerides, and cholesterol are regarded as the secondary indicators. There are safety indicators including liver enzyme and kidney function. The work such as selection of literature, data collection, quality evaluation of included literature, and assessment of publication bias will be conducted by 2 independent researchers. Meta-analysis will be performed by RevMan 5.0 software. Results: This study will provide high-quality evidence for the effectiveness and safety of HYS in the treatment of type 2 diabetes. Conclusion: The results of the study will help us determine whether HYS can effectively treat type 2 diabetes. Ethics and dissemination: This study does not require ethical approval. We will disseminate our findings by publishing results in a peer-reviewed journal. OSF registration number: DOI 10.17605/OSF.IO/AXBRV.